2020
DOI: 10.1007/s13202-020-00958-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of sequence stratigraphy for an enhanced hydrocarbon reservoirs correlation in “OSP” field Niger Delta, Nigeria

Abstract: The cost of drilling exploration and production wells is high and the price of crude oil in the capital market is fluctuating, therefore, there is the need to mitigate the risk of improper investigation of time/age-dependent reservoir rocks continuity within a field. Sequence stratigraphic analysis was carried out in OSP field with the aim of identifying and correlating hydrocarbon reservoirs that are deposited contemporaneously. Key stratigraphic surfaces (maximum flooding surfaces and sequence boundaries) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Four major sequence boundaries and three intervening Maximum Flooding Surfaces (MFS) were recognized to have been deposited within the shallow Inner-Neritic to the Middle-Neritic environments (Alege, 2017;Alege et al, 2020). Furthermore, Oyetade et al (2020) also identified key stratigraphic surfaces and depositional sequences to delineate and correlate potential hydrocarbon reservoirs in OSP field of the Niger Delta. This study seeks to improve on existing knowledge of sequence stratigraphy by delineating, correlating sequences and key stratigraphic surfaces to determine the environment of deposition of the sediments domicile in Day Field located in the onshore Central Swamp depobelt of the Niger Delta, Nigeria (Figure 1).…”
mentioning
confidence: 99%
“…Four major sequence boundaries and three intervening Maximum Flooding Surfaces (MFS) were recognized to have been deposited within the shallow Inner-Neritic to the Middle-Neritic environments (Alege, 2017;Alege et al, 2020). Furthermore, Oyetade et al (2020) also identified key stratigraphic surfaces and depositional sequences to delineate and correlate potential hydrocarbon reservoirs in OSP field of the Niger Delta. This study seeks to improve on existing knowledge of sequence stratigraphy by delineating, correlating sequences and key stratigraphic surfaces to determine the environment of deposition of the sediments domicile in Day Field located in the onshore Central Swamp depobelt of the Niger Delta, Nigeria (Figure 1).…”
mentioning
confidence: 99%